2015
DOI: 10.7759/cureus.317
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm to Predict Success of Indirect Decompression Using the Extreme Lateral Lumbar Interbody Fusion Procedure

Abstract: Purpose: The purpose of this study is to define an algorithm that will predict the success of indirect decompression without the need for direct decompression in patients undergoing lateral lumbar interbody fusions.Methods and Materials: A prospective cohort study was undertaken for patients undergoing indirect decompression with lateral lumbar interbody fusion. Patients had to meet the following criteria prior to indirect fusion: lack of facet fusion on CT, absence of free disc fragment or compressive facet j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 9 publications
0
24
0
3
Order By: Relevance
“…Sitio del estudio: un total de 5 estudios fueron realizados en Estados Unidos (13,(20)(21)(22)(23), tres en India (24)(25)(26), dos en México (27,28), dos en China (29,30) (29,32,38,41), de 28 a 37 semanas 6 casos (24,27,36,37,39) y 37 semanas o más en 4 casos (13,26,31). El método de diagnóstico fue ultrasonido prenatal en 21 casos (20,21,(23)(24)(25)27,28,30,(32)(33)(34)(35)37,40,(42)(43), y en el alumbramiento o por patología, 10 casos (13,26,29,31,36,38,39,41,43). Se ofreció terminación del embarazo en 4 casos (20,23).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Sitio del estudio: un total de 5 estudios fueron realizados en Estados Unidos (13,(20)(21)(22)(23), tres en India (24)(25)(26), dos en México (27,28), dos en China (29,30) (29,32,38,41), de 28 a 37 semanas 6 casos (24,27,36,37,39) y 37 semanas o más en 4 casos (13,26,31). El método de diagnóstico fue ultrasonido prenatal en 21 casos (20,21,(23)(24)(25)27,28,30,(32)(33)(34)(35)37,40,(42)(43), y en el alumbramiento o por patología, 10 casos (13,26,29,31,36,38,39,41,43). Se ofreció terminación del embarazo en 4 casos (20,23).…”
Section: Resultsunclassified
“…La edad gestacional al momento de la terminación del embarazo osciló entre las 15 y las 40 semanas: de 22 semanas o menos, 9 casos (20,22,23,28,40); de 23 a 27 semanas, 4 casos (29,32,34,38); de 28 a 37 semanas, 13 casos (21,24-25-26-28,30,33,36,39,41,42-43) y de 38 a 42 semanas, 5 casos (13,26,31,35,37). Respecto al tipo de parto: parto por cesárea, 12 casos (8,21,26,27,(30)(31)(32)(33)(34)39,42,43), parto vaginal, 10 casos (13,25,28,29,(35)(36)(37)41,42).…”
Section: Resultsunclassified
“…In this series, 3 indirect decompression failures (1.7%) were observed, the lowest failure rate reported in studies in which there were no apparent exclusions of patients on the basis of degree or etiology of stenosis. 1,[15][16][17] No elements of the technique, specific to the technique of ALIF in the lateral decubitus position, were identified that would otherwise allow for the relatively low rate of indirect decompression failure. 11 Rather, given the complete commitment to indirect decompression in this consecutive patient series (with no exclusions of patients based on stenosis), this rate suggests a true representation of the effectiveness of indirect decompression.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with free disc fragments, facet cysts, and severe stenosis were excluded. 17 The notion of exclusion of patients with severe spinal stenosis is an interesting one. In the most cited paper on indirect decompression in LLIF, Oliveira et al reported on 21 patients who underwent stand-alone LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, factors that are less likely to influence indirect decompression in LLIF are cage position, cage type, side of approach, Fig. 6 A 66-year-old woman suffering from contralateral iliopsoas hematoma (arrow) preoperative sagittal/coronal alignment, presence of facet arthropathy, spinal level (upper or lower lumbar spine), and number of operated spinal levels [9,21,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%